Squeezability. Part 2: getting stuff out of a bottle - Yoxall, Alaster; Kamat, Seri Rahayu; Langley, Joe (2009)
Western Europe, the USA, and Japan are experiencing rapidly ageing societies. That ageing brings with it a host of issues, not least a society in which a large proportion is likely to have relative difficulties with strength, dexterity, and cognition. One specific area that stimulates a significant amount of controversy is the accessibility and functionality of product packaging. Newspapers and television frequently report on consumer’s frustration with regard to ‘over’ packaged or poorly accessible goods. In response, researchers, designers, brand-owners, and manufacturers have been undertaking significant work to address these concerns.Developments in ‘easy to open’ packaging are all around. However, the question remains ‘how easy is easy?’ In a previous study, the authors used analytical and experimental techniques to look at accessibility of the contents of ‘squeezy’ bottles; bottles that have, in essence, been specifically designed to improve physical access to the product. This work demonstrated that ease of access is affected by a complex combination of several factors, not least of these are bottle stiffness, shape, and orifice type. This article outlines a continuation of this study, using thin-film force sensors to study grip forces applied when squeezing bottle and assessing how that force changes with gender and age. The article goes further to derive what the authors term bottle ‘efficiency’ and illustrate that this varies significantly with the bottle design.